CRYSTALLIZATION OF MELILITE FROM CMAS-LIQUIDS AND THE FORMATION OF THE MELILITE MANTLE OF TYPE B1 CAIS: EXPERIMENTAL SIMULATIONS - Mendybaev R.A.; Richter F.M.; Davis A.M. (My University, 2006)
Type B CAIs are subdivided into B1s, with well-developed melilite mantles, and B2s, with randomly distributed melilite. Despite intensive study, the origin of the characteristic melilite mantle of the B1s remains unclear. Recently, we proposed that formation of the melilite mantle is caused by depletion of the droplet surface in volatile magnesium and silicon due to higher evaporation rates of volatile species compared to their slow diffusion rates in the melt, thus making possible crystallization of melilite at the edge of the CAI first, followed by its crystallization in the central parts at lower temperatures. Here, we present the results of an experimental study that aimed to reproduce the texture observed in natural Type B CAIs. First, we experimentally determined crystallization temperatures of melilite for three melt compositions, which, combined with literature data, allowed us to find a simple relationship between the melt composition, crystallization temperature, and composition of first crystallizing melilite. Second, we conducted a series of evaporation and cooling experiments exposing CAI-like melts to gas mixtures with different oxygen fugacities ( fO2 ). Cooling of the molten droplets in gases with log fO2 {greater than or slanted equal to} IW - 4 resulted in crystallization of randomly distributed melilite, while under more reducing conditions, melilite mantles have been formed. Chemical profiles through samples quenched right before melilite started to crystallize showed no chemical gradients in samples exposed to relatively oxidizing gases ( log fO2 {greater than or slanted equal to} IW - 4 ), while the near-surface parts of the samples exposed to very reducing gases ( log fO2 {less-than or slanted equal to} IW - 7 ) were depleted in volatile MgO and SiO2, and enriched in refractory Al2O3. Using these experimental results and the fact that the evaporation rate of magnesium and silicon from CAI-like melts is proportional to sqrt(PH2), we estimate that Type B1 CAIs could be formed by evaporation of a partially molten precursor in a gas of solar composition with PH2 {greater than or slanted equal to} 10-4 bar. Type B2 CAIs could form by slower evaporation of the same precursors in the same gas with PH2 {less-than or slanted equal to} 10- 5 bar. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CHEMICAL COMPOSITION; CRYSTALLIZATION; MAGNESIUM; MELILITE; SILICON; SOROSILICATE